Inventoring Factors of Building Licensing Processes in Gianyar District - made dwipa arta; Nyoman Budiartha; Ngakan Ketut Acwin Dwijendra; A.A.Gde Agung Yana (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2021)
This study examines the factors that building owners do not apply for a building permit (IMB) in Gianyar Regency. The sample in this study were building owners who did not take care of IMB in Gianyar Regency with a total population of 285 people with a random sample of 25 samples of requests for information on spatial planning that could potentially take care of building IMB. This research was conducted by collecting data by means of observation, interviews and questionnaires with the Delphi method as an analysis technique. The results show that there are 5 factors that influence building owners not taking care of building permits in Gianyar Regency, namely not knowing the IMB rules, no fees to take care of the IMB, processing the old IMB and difficult procedures, insufficient administrative requirements and no time to take care of the IMB. The factor that most influences building owners is that there is no fee to arrange a building permit. Obstacles in managing the IMB are 1) The community does not understand the procedure, 2) The community is not prepared to pay IMB levies, 3) The community is deliberate to violate the applicable rules 4) complaints of no cost, 5) expensive IMB 6) There is no timeliness 7) lack of socialization and lack of supervisors in the field so that new buildings are still found without permits